Zespół Hakima-Adamsa u 61-letniego pacjenta - opis przypadku = Hakim-Adams syndrome in an 61-year-old patient - case report - Kamila Woźniak; Dorota Ratuszek-Sadowska; Maciej Śniegocki (Kazimierz Wielki University, 2016)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Śniegocki Maciej. Zespół Hakima-Adamsa u 61-letniego pacjenta - opis przypadku = Hakim-Adams syndrome in an 61-year-old patient - case report. Journal of Education, Health and Sport. 2016;6(9):268-275. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61746 http://ojs.ukw.edu.pl/index.php/johs/article/view/3803       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016.     Zespół Hakima-Adamsa u 61-letniego pacjenta - opis przypadku   Hakim-Adams syndrome in an 61-year-old patient - case report   Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Maciej Śniegocki1 1.        Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2.        Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu     Streszczenie   Wodogłowie normotensyjne (normociśnieniowe) to postać wodogłowia komunikującego (hydrocephalus communicans), przebiegającego z prawidłowym ciśnieniem płynu mózgowo - rdzeniowego z okresowymi zwyżkami. Opisane zostało po raz pierwszy przez Solomona Hakima w 1965 roku (zespół Hakima-Adamsa). Przyczyny zespołu Hakima-Adamsa upatruje się w zaburzeniu wchłaniania płynu mózgowo - rdzeniowego. Wystąpienie choroby czasem jest poprzedzane urazem głowy. Wodogłowie normotensyjne cechuje triada objawów (tzw. triada Hakima). Stosuje się leczenie operacyjne - implantację zastawki niskociśnieniowej z wytworzeniem połączenia komorowo - otrzewnowego. Autorzy przedstawiają opis przypadku klinicznego 61-letniego pacjenta leczonego operacyjnie w Klinice Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej Szpitala Uniwersyteckiego nr 1 im. dr A. Jurasza w Bydgoszczy z rozpoznanym w badaniu obrazowym wodogłowiem normociśnieniowym oraz torbielą pajęczynówki w okolicy nadsiodłowej.   Słowa kluczowe: wodogłowie normotensyjne, NPH, zespół Hakima-Adamsa, triada Hakima.     Abstract   Normal pressure hydrocephalus (NPH) is a form of communicating hydrocephalus (hydrocephalus communicans) that runs with normal pressure of cerebrospinal fluid with periodic advances. First described by Solomon Hakim in 1965 (Hakim-Adams syndrome). Hakim-Adams syndrome causes of the disorder is seen in the absorption of cerebrospinal fluid. The disease is sometimes preceded by a head injury. NPH is characterized by a triad of symptoms (Hakim's triad). Apply surgery - implantation of the valve low pressure to form a combination kiln-peritoneal. The authors present a case of 61-year-old patient operating treated in the Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery, Dr Antoni Jurasz University Hospital No.1 in Bydgoszcz imaging test diagnosed with normal pressure hydrocephalus and suprasellar arachnoid cysts.   Key words: normal pressure hydrocephalus, NPH, Hakim-Adams syndrome, Hakim's triad.